Introduction to molecular magnetism : from transition metals to lanthanides - Benelli, Cristiano; Gatteschi, Dante (Wiley-VCH Verlag GmbH & Co. KGaA, 2015)
This first introduction to the rapidly growing field of molecular magnetism is written with Masters and PhD students in mind, while postdocs and other newcomers will also find it an extremely useful guide. Adopting a clear didactic approach, the authors cover the fundamental concepts, providing many examples and give an overview of the most important techniques and key applications. Although the focus is one lanthanide ions, thus reflecting the current research in the field, the principles and the methods equally apply to other systems. The result is an excellent textbook from both a scientific and pedagogic point of view.